An historical instance of urban unsustainability that astounds to this day. (13th April 2021) - Mella, Piero; Gazzola, Patrizia
Abstract: The aim of the paper is to present how the interaction between the micro behaviours of individual families and the collective macro behaviour of the city of Pavia produced a unique historical phenomenon that, on the one hand, has amazed Italy and the whole world for its striking number of towers and on the other represents a clear example of urban housing unsustainability in the Middle Ages. In the paper, using a simulation software, the micro and macro effects of the accumulation of towers in the city of Pavia are shown. The study of the behaviour of collectivities has been a very complex subject of analysis and for this reason, a fascinating and interesting one as well. To understand, explain and, to a certain extent, control collective phenomena, the Theory of Combinatory Systems was recently formalized. This theory describes, interprets and simulates the most relevant collective phenomena and their observable effects. With the aid of a simple probabilistic combinatory automaton, we have simulated the dynamics of the formation of the towered town of Pavia, Italy, which is unique in all the world, as can be observed in the historical descriptions or by a visit to this ancient Italian town.